PRELIMINARY MEASUREMENT OF HIGH-FREQUENCY ELECTRICAL CONDUCTIVITY OF ANTARCTIC ICE WITH AC-ECM TECHNIQUE - スギヤマ, ケン; フジタ, シュウジ; スエオカ, シゲル; マエ, シンジ; ホンドウ, タケオ; SUGIYAMA, Ken; FUJITA, Shuji; SUEOKA, Shigeru; MAE, Shinji; HONDOH, Takeo (National Institute of Polar Research, 1995)
P(論文) We measured the high-frequency electrical conductivity of solid ice samples collected in the Antarctic ice sheet with a new technique called "AC-ECM (AC Electrical Conductivity Measurements)". The purpose was to establish a new convenient technique to detect variation of impurity content in ice cores with high spatial resolution and with high reproducibility for repetitive measurements. For this purpose, the conductance of the ice sample was measured with 2-terminal electrodes and with parallel-plate electrodes at 16 frequencies between 40Hz and 1MHz. Then both results of the conductance measured by these two different pairs of electrodes were compared to discuss the physical meaning of the signals measured with the new technique. The preliminary measurements were successful. We could measure conductance, which is proportional to the conductivity of ice, at frequencies above 100kHz at -20℃. The relaxation frequencies of Debye dispersion were higher when values of conductance were measured with the new technique, which suggested that surface conduction was dominant. departmental bulletin paper